The safest lies - Miranda, Megan (Crown Books for Young Readers, 2016)
"When Kelsey's agoraphobic mother disappears after years of claiming the kidnappers she escaped from were coming back for her, Kelsey quickly discovers that her mother isn't who she thought she was -- and she's not the abductor's only target"--